Theory and design consideration of a THz superradiant waveguide FEL - Weinberg, Amir; Gover, Avraham; Nause, Ariel; Friedman, Aharon; Ianconescu, Reuven; Fisher, Andrew; Musumeci, Pietro; Fukasawa, Atsushi; Rosenzweig, James (Frontiers in Physics, 2024)
We present theoretical analysis and design considerations of a THz superradiant FEL. We derive analytical expressions for the spectral parameter of THz radiation, emitted superradiantly in a rectangular waveguide using a LSM (Longitudinal Section Magnetic) mode expansion. The results compare well with numerical simulations using UCLA GPTFEL code. GPT simulations of the accelerator e-beam transport show that the chirp provided by a hybrid photocathode RF gun, can produce tight bunching at the undulator site below 𝜎=100fs. This enables intense superradiant emission up to 3THz, limited by the beam bunching factor. Phase-space analysis of the beam transport indicates that keeping the beam bunching parameter small enough for higher THz frequency operation is limited by the energy spread of the beam in the gun.